Analisis Pemahaman Siswa Terhadap Menulis Teks Eksplanasi dalam Pembelajaran Bahasa Indonesia - Meyshi Fauziah; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Writing skills according to experts in learning Indonesian are placed at the highest level of learning in the language acquisition process. One form of text that is important to learn in schools for writing skills is explanatory text. Explanatory text is a text that explains the process of a natural, social or cultural phenomenon logically and systematically. . Writing is one of the language skills that must be mastered by students. . However, in reality, there are still many students who have difficulty in understanding and writing explanatory texts. This study aims to analyze students' understanding of explanatory texts and students' abilities in writing explanatory texts in learning Indonesian in grade VI of elementary school. the number of samples in this study was 5 grade VI students. In this study, the researcher used a qualitative descriptive method. the results of this study indicate that students' understanding of writing explanatory texts is still low.